Evaluating the recycling efficiency of industrial water use systems in China: Basin differences and factor analysis. (15th August 2022) - Zhuang, Yuan; Zhang, Lina; Chiu, Yung-ho; Guo, Zhiqin; Chu, Yu; Du, Xinya
Abstract: Numerous studies have divided industrial water use system into stages of industrial water use (IWU) and wastewater treatment (IWT) subsystems, named as the IWUWT system, yet scant studies have examined its dynamic recycling efficiency with non-discretionary variables. This paper proposes a dynamic two-stage recycling model with non-discretionary variables to compare and analyze the basin differences of the efficiency, and further reveal the driving forces of this efficiency in the Yangtze River basin and Yellow River basin. The results are as follows. (1) The average overall efficiency of the IWUWT system for the 30 provinces during 2011–2018 was 0.79 due to the bad performance of the IWT subsystem with an efficiency score of 0.74, especially for Yunnan and Guangxi. (2) The influence of economic policy uncertainty on circulating industrial water use is more significant in the south basin. (3) Economic development and water use intensity were the main drivers of IWUWT efficiency in the Yangtze River basin, while economic development and environmental consciousness were for the Yellow River basin. The results have important implications for Chinese government and different provinces to improve IWUWT efficiency by policy-making. Highlights: A dynamic two-stage recycling model with non-discretionary variables is proposed. Basin differences of the IWUWT efficiency and its stage efficiencies are provided. Driving factors of the IWUWT efficiency in typical river basins are revealed. The influences of EPU on IWUWT efficiency are highlighted.